2020
DOI: 10.3390/ijerph17165737
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships of Parenting Information, Family Care, and Child Development: A Cross-Sectional Study in Rural China

Abstract: This paper studied the interrelationships between parenting information, family care, and early childhood development (ECD) outcomes. A total of 1787 sample households in rural China were enrolled in a cross-sectional study. A demographic questionnaire, a parenting information questionnaire, the Family Care Indicators (FCIs), and the Bayley Scales of Infant Development version III (BSID-III) were used to measure demographic characteristics, parenting information that the caregiver received, family care, and ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…India was the only site with no associations between any of the FCI and IYCF indicators. While previous studies have not looked at FCI in relation to nutrition, published data have reported positive associations between FCI scores and IQ and other indicators of early child development (Rubio‐Codina & Grantham‐McGregor, 2020 ; Zhong & Luo, 2020 ). Similarly, previous research on responsive feeding found associations with better child nutrition (Black & Aboud, 2011 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…India was the only site with no associations between any of the FCI and IYCF indicators. While previous studies have not looked at FCI in relation to nutrition, published data have reported positive associations between FCI scores and IQ and other indicators of early child development (Rubio‐Codina & Grantham‐McGregor, 2020 ; Zhong & Luo, 2020 ). Similarly, previous research on responsive feeding found associations with better child nutrition (Black & Aboud, 2011 ).…”
Section: Discussionmentioning
confidence: 98%
“…Higher FCI scores have been associated with better cognitive development in young children (Rubio‐Codina & Grantham‐McGregor, 2020 ; Zhong & Luo, 2020 ). Responsive feeding offers an important opportunity for young children to interact with their caregivers and improve their nutritional status (Black & Aboud, 2011 ).…”
Section: Introductionmentioning
confidence: 99%